Advances in the application of echocardiography in septic cardiomyopathy - LIN Huan*, REN Hongsheng (Zhongguo linchuang yanjiu)
Septic cardiomyopathy (SCM) is an acute heart dysfunction caused by sepsis. Literature reports its incidence fluctuating between 13.8% and 60.0%, with a high mortality rate of 70% to 90%. Currently, there is no gold standard for diagnosis, nor specific indicators to assess prognosis. Echocardiography is widely used in SCM research due to its advantages of visualization, non-invasiveness, bedside operation, and reproducibility. Different types of ultrasounds have unique characteristics, for example, conventional echocardiography hardware is well-established with easily obtainable parameters, transesophageal echocardiography provides more accurate parameters, and speckle tracking echocardiography has high sensitivity. This article summarizes and reviews the application of echocardiographic techniques in SCM in recent years, aiming to provide clinical doctors with reference for early diagnosis and prognostic assessment of SCM.